The impact of crisis management on brand reputation and brand positioning towards the performance of upscale hotels in the post-COVID-19 era / Agus Riyadi - Riyadi, Agus (2023)
Since the pandemic, the hotel industry has been one of the sectors hardest hit. Quarantine, physical distancing, and travel restrictions have caused substantial problems for the hotel industry. To capitalize on the anticipated post-COVID-19 travel boom, hotel operators must swiftly promote their new protocol products and services in response to shifting customer behavior and new norm requirements. It is, therefore, essential to investigate crisis management in terms of how hotel brands can adapt to new norms. This study empirically investigates crisis response brands created by hotels in Indonesia to help them survive the COVID-19 outbreak. Consequently, this study aims to investigate the effect of crisis management on brand performance as influenced by brand reputation and positioning. Crisis management was assessed by signal detection, preparation and prevention, recovery, and learning process as grounded in situational crisis communication theory (SCCT), adding to the body of the crisis management literature. Evaluation of the brand in the aftermath of the COVID-19 pandemic can be an effective method for managing brand reputation, brand positioning, and brand performance. A quantitative cross-sectional survey was adopted to understand crisis management and brand better. The sample for this study consisted of 341 hotel managers from the Indonesian Hotel General Manager Association members participated in this study. The results were analyzed using the Structure Equation Modelling (SEM) via AMOS (version 23.0). Findings showed that crisis management has no direct significant influence on brand performance. This research confirms that the mediating influence of brand reputation and brand positioning will positively influence crisis management and brand performance. This study extends current crisis management and brand performance research, especially in the hotel industry. In light of this finding, hotel managers should not ignore or be ignorant of crisis mitigation and brand management, particularly in terms of brand reputation, brand positioning, and brand performance.